Innovative Work Behavior Development Through Technopreneurship Leadership in Vocational Schools: An Mixed Method Explanatory Research - Rahmawati, Ima; Lestari, Hana; Permana, Johar; Kurniatun, Taufani Chusnul (Jurnal Pendidikan Progresif, 2022)
Objectives: This study explores the development of innovative work behavior through technopreneurship leadership. Methods: Explanatory mixed method with quantitative data collection in the form of questionnaires through a survey of 267 permanent teachers of foundations at private vocational schools in Bogor City and analyzed descriptively. Meanwhile, qualitative data collection in the form of interviews, observations, and documentation were analyzed using the Atlas Ti application. Findings: The results of this study indicate that to be able to develop innovative work behavior it is necessary to be supported by the ability of leaders in digital understanding and entrepreneurial skills in developing work programs in vocational schools. So with the abilities possessed by technopreneurship leaders, they will be able to influence the creation of a creative and innovative environment. Conclusion: Technopreneurship's leadership ability makes a new model of leadership in the future, especially in the development of innovative work behavior. Keywords: innovative work behavior, technopreneurship leadership, vocational teachers.DOI: http://dx.doi.org/10.23960/jpp.v12.i2.202242